Canale, G. (2019). Technology, Multimodality and Learning: Analyzing meaning across scales (Revista Latinoamericana de Estudios del Discurso, 2020)
Canale, Germán, 2019Technology, Multimodality and Learning: Analyzing meaning across scalesSerie: Palgrave Studies in Educational Media.266 pp. New York, EEUU: Palgrave MacMillan.ISBN: 978-3-030-21795-2.